2023
DOI: 10.1002/tox.23898
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA nuclear receptor interacting protein 1 promoted biliary tract cancer epithelial‐mesenchymal transition and stemness by regulating the miR‐515‐5p/AKT2 axis and PI3K/AKT/mTOR signaling pathway

Abstract: Biliary tract cancer (BTC) is a devastating malignancy that is notoriously difficult to diagnose and is associated with high mortality. Circular RNA (circRNA) is a class of endogenous non‐coding RNA which has been regarded as the key regulator of tumor initiation and progression, including BTC. Circular RNA nuclear receptor interacting protein 1 (circ_NRIP1), as a circular RNA, is abnormally expressed in many human tumors and exhibits diverse functions in cancer progression. However, its biological significanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Notably, RBPs constitute a large class of proteins involved in the regulation of transcript splicing, transport, modification, stability, and translation ( 34 , 36 ) ( Figure 3B ). A growing body of research has shown the significant therapeutic potential of circRNA-RBP interaction, as well as its critical involvement in the onset and progression of many cancers ( 37 39 ). For example, through luciferase and RNA pull-down assays, Tang et al.…”
Section: Biological Functions Of Circrnamentioning
confidence: 99%
“…Notably, RBPs constitute a large class of proteins involved in the regulation of transcript splicing, transport, modification, stability, and translation ( 34 , 36 ) ( Figure 3B ). A growing body of research has shown the significant therapeutic potential of circRNA-RBP interaction, as well as its critical involvement in the onset and progression of many cancers ( 37 39 ). For example, through luciferase and RNA pull-down assays, Tang et al.…”
Section: Biological Functions Of Circrnamentioning
confidence: 99%